Pravova ohorona bìorìznomanìttâu strategìčnih dokumentah Ukraïni - Vaŝišin, Marìâ (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The author analyzes the basic principles of the state environmental policy of Ukraine in the field of biodiversity protection. Attention is drawn to the fact that the integration of environmental policy in the decision-making process on socio-economic developmentof Ukraine is carried out by including issues of the values of biodiversity in national, local, strategic, policy documents and plans for economic development. It is emphasized that the development of spatial planning and economic activities should be consistent with environmental requirements, and the legislation on strategic environmental assessment (SEA) and environmental impact assessment (EIA) should be taken into account. It is underlined that SEA is a modern and effective tool that can predict the consequences for the environment, identify threats to biodiversity, historical and cultural heritage and public health from the implementation of state planning documents, offer alternatives and develop measures to prevent or reduce possible negative consequences for the environment. The author believes that the national environmental policy should not only be consistent with the obligations set out in the European Union Association Agreement on the implementation of mandatory EU Directives for Ukraine in the field of environmental protection, but it should also focus on new strategic vectors of EU environmental policy, particularly the EU’s biodiversity strategy for 2030. The importance and urgency of developing and implementing a new general scheme of planning of the territory of Ukraine on the basis of leading geographic information technologies is proved. These technologies will form a framework for a national geographic information system of coordinated and transparent governance in all areas, including environmental protection. It is underlined that the modern strategic direction of the state ecological policy of Ukraine should be a comprehensive approach to determining the extent of environmental damage caused by the military aggression of the Russian Federation on the territory of Ukraine and proper recording of all instances of environmental crimes committed by the occupiers.
Keywords: state environmental policy; environmental law; sustainable development; ecological network; strategic environmental assessment; deržavna ekologìčna polìtika; ekologìčne pravo; stalij rozvitok; ekologìčna mereža; strategìčna ekologìčna ocìnka